RZUT OKA NA POLSKĄ ROMANISTYKĘ W PIERWSZYM DZIESIĘCIOLECIU XXI WIEKU - Zabłocka, Maria (Zeszyty Prawnicze, 2016)
An Overview of the Work of Polish Scholarship on Roman Law in the First Decade of the Twenty-First Century Summary In the first decade of the 21st century Polish scholars of Roman Law accomplished a considerable amount of work, adopting an entirely new area of research. While publications on private law had constituted the predominant trend since the Second World War, especially in the first forty years of the period, articles on public law were an exception until recent times. In the last few years nearly twice as many monographs have been published on a broad range of issues in public law, such as the political system, administration, and criminal law, as on private law. The numer of articles on public law has also been much larger than on other branches of Roman law. The work of Polish Romanists has earned acknowledgement abroad, as evidenced by the invitations Polish researchers have been receiving to contribute to foreign occasional volumes, and by the digests of Polish books and articles which have appeared in the Italian scholarly journal «Iura. Rivista internazionale di diritto romano e antico».